RESEARCH ON SUSTAINABLE DEVELOPMENT OF CHINESE DIRECT INVESTMENT IN COUNTRIES OF THE “ONE BELT, ONE ROAD” INITIATIVE (INNOVATIVE ECONOMY, 2025)
Ye Jianfu. RESEARCH ON SUSTAINABLE DEVELOPMENT OF CHINESE DIRECT INVESTMENT IN COUNTRIES OF THE “ONE BELT, ONE ROAD” INITIATIVEPurpose. The aim of the article is to consider China’s direct investments in “One Belt, One Road” Initiative countries, analysing their volumes, directions, sectors, and geographic distribution, while assessing their economic, social, and environmental impacts on partner nations, identifying challenges, and proposing solutions to enhance sustainable development.Methodology of research. The following methods were employed during the research process: Collect, analyse, and compare literature analysis methods suitable for constructing a theoretical framework for China’s investment in the “One Belt, One Road” Initiative, and formulate effective suggestions for the challenges and opportunities in the sustainable development process of the “One Belt, One Road” Initiative, formulate relevant policy recommendations and cooperation mechanisms; as well as the application of visual analysis methods.Findings. It was established that China’s direct investment along the “One Belt, One Road” Initiative encounters significant challenges across multiple domains. It was substantiated that political, economic, and legal risks pose major concerns for investment sustainability. It was proven that current risk management systems and early warning mechanisms require substantial strengthening. The relevance of improving mechanisms for political support and cooperation, which will contribute to overall stability, was also analysed. The importance of creating a transparent and predictable investment environment as a factor of long-term success was emphasized.Originality. The study highlights the importance of effective coordination between government, businesses, and society civil society to ensure sustainable investment development within the initiative. The proposed approach differs from existing models in more integrated policy implementation. The research demonstrates that government plays a fundamental role in providing policy support and promoting international cooperation.At the same time, it is proven that companies need to improve risk management mechanisms and increase the level of social responsibility. The study also deepens the understanding of the role of society in building trust and developing interstate dialogue, which contributes to stabilizing the investment climate.It confirms that enterprises must enhance their risk management and social responsibility mechanisms. Furthermore, it advances our understanding of society’s critical function in building trust and fostering communication between participating nations, which leads to more stable investment environments.Practical value. The research findings have direct practical applications across multiple domains. Government policymakers can use these insights to develop more effective investment policies and risk management frameworks. Financial institutions can enhance their assessment models for “One Belt, One Road” projects. Companies planning investments in “One Belt, One Road” countries can better evaluate risks and opportunities. Local governments in recipient countries can leverage this research to optimize their investment facilitation policies – maximizing the benefits of Chinese enterprises’ investments while ensuring environmental and social sustainability.Key words: “One Belt, One Road”, investment facilitation level, foreign direct investment, investment openness, cooperation mechanisms, challenges and countermeasures.
Keywords: “One Belt, One Road”; investment facilitation level; foreign direct investment; investment openness; cooperation mechanisms; challenges and countermeasures